Efficacy of injury prevention related coach education within netball and soccer - Gianotti, S.; Hume, P. A.; Tunstall, H. (Journal of Science and Medicine in Sport, 2010)
In 2004, Netball New Zealand and New Zealand Football adapted a generic 10-point action plan for sports injury prevention, SportSmart, to create NetballSmart and SoccerSmart, as part of their coach education programmes. A small-size descriptive study was conducted in both sports, to assess the efficacy of integrating sports injury prevention into coach education. NetballSmart was evaluated at the end of 2005, via a telephone survey of 217 coaches (53% response rate) who had attended a NetballSmart course earlier in the year. SoccerSmart was evaluated at the start of 2007, via an Internet questionnaire completed by 71 coaches (20% response rate) who had attended a SoccerSmart course in 2006. The evaluations focused on the quality and use of the course resource material, as well as assessing the extent to which coaches had incorporated injury prevention behaviours into player practices. After attending a NetballSmart course, 89% of coaches changed the way they coached, with 95% reported using knowledge from the course and passing it on to players. Ninety-six percent of football/soccer coaches also changed the way they coached, with most change relating to warm-up/cool-down and stretch (65%), technique (63%), fitness (60%) and nutrition/hydration (58%) practices. Although this was a descriptive study in nature, with a small sample size, we conclude that integration of injury prevention content within coach education courses and resources may be a viable and effective strategy to help community coaches - and therefore community players - help reduce their risk of injury.